2022
DOI: 10.1177/00111287221074942
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in Calls for Police Service During COVID-19: Evidence From China

Abstract: This study examined the temporal variations in calls for service before, during, and after the COVID-19 pandemic lockdown in China using a sample of 37,124 police service calls made from January 1, 2019, to December 31, 2020 to a 110 command center in a county-level city in Hubei Province. There was a significant temporal effect, and the calls for service peaked between 08:00 and 19:59 throughout the entire period. The busiest hours of the day for calls for police service were between 12:00 and 19:59, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Data included all calls for service made from January 1, 2019 through December 31, 2020 (with the lockdown occurring January 24, 2020 through March 16, 2020), representing over 37,000 unique records), including violent, property, public order, traffic-related, domestic violence, dispute-related, and “other” calls. Dai et al (2022) find violent, property, and dispute case crimes declined during the lockdown, while public order, domestic violence, and “other” crimes increased, and traffic-related crimes nearly disappeared. Importantly, whether and the extent to which the rates at which crimes returned to pre-lockdown levels differed by crime type.…”
Section: Changes In Crime Counts and Calls For Servicementioning
confidence: 94%
See 3 more Smart Citations
“…Data included all calls for service made from January 1, 2019 through December 31, 2020 (with the lockdown occurring January 24, 2020 through March 16, 2020), representing over 37,000 unique records), including violent, property, public order, traffic-related, domestic violence, dispute-related, and “other” calls. Dai et al (2022) find violent, property, and dispute case crimes declined during the lockdown, while public order, domestic violence, and “other” crimes increased, and traffic-related crimes nearly disappeared. Importantly, whether and the extent to which the rates at which crimes returned to pre-lockdown levels differed by crime type.…”
Section: Changes In Crime Counts and Calls For Servicementioning
confidence: 94%
“…Importantly, whether and the extent to which the rates at which crimes returned to pre-lockdown levels differed by crime type. Temporal patterns changed as well, as Dai et al (2022) found that compared to pre- and post-lockdown, most police service calls during the lockdown began to increase in the morning and then peaked between 12:00 and 3:59 p.m. during the lockdown, meaning that the pandemic changed the timing of calls. Interestingly, no significant changes in temporal pattern were found for domestic violence calls, and only traffic-related calls evidenced changes based on the day of the week of those calls.…”
Section: Changes In Crime Counts and Calls For Servicementioning
confidence: 99%
See 2 more Smart Citations
“…Different regions also have their own condition and thus varied differently. By comparing over 37,000 unique records from 2019 to 2020 in China, Dai et al discovered that during the lockdown, although domestic violence significantly increased, the dispute cases decreased [6]. The previous study by Mohler et al showed that there was a significant increase in domestic violence in Los Angeles from January to April 2020 [7].…”
Section: Introductionmentioning
confidence: 99%